Advertisement Remove all ads

Check whether the following is the quadratic equations: (2x - 1)(x - 3) = (x + 5)(x - 1) - Mathematics

Check whether the following is the quadratic equations: (2x - 1)(x - 3) = (x + 5)(x - 1)

Advertisement Remove all ads

Solution

(2x - 1)(x - 3) = (x + 5)(x - 1)

⇒ 2x- 7x + 3 = x+ 4- 5

⇒ x- 11x + 8 = 0

It is of the form ax2 + bx + c = 0.

Hence, the given equation is quadratic equation.

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

NCERT Class 10 Maths
Chapter 4 Quadratic Equations
Exercise 4.1 | Q 1.5 | Page 73
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×